VOLODYMYR BAZYLEVSKYI: AN INCONVENIENT FIGURE - Baran, Evgen (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
The article explores the life and work of the Ukrainian poet and essayist, laureate of the 1995 Shevchenko Prize, Volodymyr Bazylevskyi (1937–2026). It recounts the beginnings of a personal acquaintance with the writer and presents a selection of his letters addressed to Yevhen Baran.